Appraisals of Wildlife During Restorative Opportunities in Local Natural Settings - Johansson, Maria; Flykt, Anders; Frank, Jens; Hartig, Terry (Frontiers in Environmental Science, 2021)
Many call for a broad approach to valuation of nature’s contribution to people, one that provides a contextualized understanding of what may be experienced as a value in different cultures, groups and settings. In the present paper we address contributions of nature to psychological well-being as realized through restorative processes during encounters with wildlife. Although restorative benefits of nature experience have received much consideration, sparse attention has been given to the role of the presence or absence of different animals in the settings investigated. The presence of a liked species may increase appreciation for and engagement with a natural setting, but fear of encountering some species may counter the desire to visit a setting with otherwise high restorative quality. This paper proposes a psychological framework for understanding how wildlife may contribute to or hinder people’s opportunities to restore in local natural settings. The framework addresses the transaction between the individual and their surroundings, making use of an appraisal theory of emotion and theories about the restorative benefits of nature experience. We focus upon encounters in landscapes shared by humans and wildlife, and we elaborate on our reasoning with scenarios from Sweden involving local people’s appraisal of wolves and roe deer. An integrated understanding of the psychological processes at work would facilitate communication and decision-making about the contribution of wildlife in nature conservation and management.